2019
DOI: 10.1055/s-0039-3401979
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Insurance

Abstract: India has healthcare expenditure of more than 5 billion dollars on diabetes-related healthcare management. Globally, approximately 12% of health expenditure is spent on diabetes and related comorbidities. Hospitalization includes hospital and laboratory expenses and cost of medications as the direct cost. India is among the countries, where if the insured dies during the time period specified in the insurance policy and the policy is active, or in force, then a death benefit will be paid. Studies in India repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Low-income people as compared to high-income people are much more likely to skip care because of financial reasons (Yip and Mahal, 2008). For the people who had insurance cover at some point of time, it has been reported that only 21.3% of high income group people and 6.4% of low income group people are actually able to get their medical reimbursement because their medication period falls beyond the coverage period (Ghosh et al, 2019). Hence, it has been observed that health insurance should have reasonable premium so that it can be made affordable for people with low purchasing power (V. Babu, 2020).…”
Section: Literature Surveymentioning
confidence: 99%
“…Low-income people as compared to high-income people are much more likely to skip care because of financial reasons (Yip and Mahal, 2008). For the people who had insurance cover at some point of time, it has been reported that only 21.3% of high income group people and 6.4% of low income group people are actually able to get their medical reimbursement because their medication period falls beyond the coverage period (Ghosh et al, 2019). Hence, it has been observed that health insurance should have reasonable premium so that it can be made affordable for people with low purchasing power (V. Babu, 2020).…”
Section: Literature Surveymentioning
confidence: 99%